The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1051/e3sconf/202017207003
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal Behaviour of Ventilation Cavities in Highly Insulated Envelopes

Abstract: This article presents long-term experimental studies on the moisture safety in the ventilation cavities of highly insulated (HI) structures. The tested HI-walls had thermal transmittances of 0.11-0.13 W/m2K. A wall with a thermal transmittance of 0.23 W/m2K represented the baseline wall in the test. In addition to walls, an HI-roof of a newly built house with a U-value of 0.08 W/m2K was measured. The results indicate that, in the ventilation cavity, the relative humidity of an HI-wall exceeds 1-7% of the humid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 6 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…It has been experimentally found that the temperature in the cavities of HI walls is close to, but slightly above, the outdoor temperature (Viljanen et al, 2020). The difference in the thermal behavior leads to a slightly higher relative humidity (RH) in the cavities of HI assemblies compared to a baseline (BL) wall, which may increase the risk of moisture damage (Viljanen et al, 2020). However, mold growth was observed at the bottom of the cavity battens of both HI and BL walls, for which the fundamental causes remained unresolved.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…It has been experimentally found that the temperature in the cavities of HI walls is close to, but slightly above, the outdoor temperature (Viljanen et al, 2020). The difference in the thermal behavior leads to a slightly higher relative humidity (RH) in the cavities of HI assemblies compared to a baseline (BL) wall, which may increase the risk of moisture damage (Viljanen et al, 2020). However, mold growth was observed at the bottom of the cavity battens of both HI and BL walls, for which the fundamental causes remained unresolved.…”
Section: Introductionmentioning
confidence: 93%
“…The recession classes are 1 (strong), 0.5 (significant), 0.25 (relatively low), and 0.1 (almost no decline). The values for the sensitivity and recession classes represented in Figures 5(d), 6, and 8(d), were selected based on the materials in the assemblies (Viljanen et al, 2020). A laboratory test was assembled to define the pressure losses of some common cavity and gap types of walls and roofs ( Figure 3).…”
Section: Studies On the Experimental Structures And The Determinationmentioning
confidence: 99%
See 3 more Smart Citations